2008
DOI: 10.1158/0008-5472.can-08-2232
|View full text |Cite
|
Sign up to set email alerts
|

A Dietary Anthocyanidin Delphinidin Induces Apoptosis of Human Prostate Cancer PC3 Cells In vitro and In vivo: Involvement of Nuclear Factor-κB Signaling

Abstract: Delphinidin, a major anthocyanidin present in many pigmented fruits and vegetables, possesses antioxidant, anti-inflammatory, and antiangiogenic properties. In this study, we provide evidence that it could be developed as a novel agent against human prostate cancer (PCa). We observed that delphinidin treatment to human PCa LNCaP, C4-2, 22Rν1, and PC3 cells resulted in a dose-dependent inhibition of cell growth without having any substantial effect on normal human prostate epithelial cells. We selected PC3 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
160
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(178 citation statements)
references
References 45 publications
14
160
1
3
Order By: Relevance
“…6,7 These berries, because of their high content in anthocyanins, are being studied also for their ability to protect against oral, 8 colon, 9,10 breast, 8 and prostate 11,12 cancer. The objectives of this study were (1) to determine the contents of total flavonoids, procyanidins, anthocyanins, and polyphenols of chokeberry extracts obtained from three cultivars and to characterize their anthocyanin fraction by high-performance liquid chromatography (HPLC) analysis, (2) to measure and compare the antioxidant activity using three different single electron transfer (SET)-based assays [2,2 0 -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ferric reducing antioxidant power (FRAP), and cupric ion reducing antioxidant capacity (CUPRAC)], one hydrogen atom transfer (HAT)-based method (oxygen radical absorbance capacity [ORAC]), and the H 2 O 2 scavenging potential (HPS) assay, and (3) to evaluate the cytotoxic action and the pro-oxidative effect of the anthocyanin fraction on the HeLa tumor cervical cell line.…”
Section: Introduction Tmentioning
confidence: 99%
“…6,7 These berries, because of their high content in anthocyanins, are being studied also for their ability to protect against oral, 8 colon, 9,10 breast, 8 and prostate 11,12 cancer. The objectives of this study were (1) to determine the contents of total flavonoids, procyanidins, anthocyanins, and polyphenols of chokeberry extracts obtained from three cultivars and to characterize their anthocyanin fraction by high-performance liquid chromatography (HPLC) analysis, (2) to measure and compare the antioxidant activity using three different single electron transfer (SET)-based assays [2,2 0 -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ferric reducing antioxidant power (FRAP), and cupric ion reducing antioxidant capacity (CUPRAC)], one hydrogen atom transfer (HAT)-based method (oxygen radical absorbance capacity [ORAC]), and the H 2 O 2 scavenging potential (HPS) assay, and (3) to evaluate the cytotoxic action and the pro-oxidative effect of the anthocyanin fraction on the HeLa tumor cervical cell line.…”
Section: Introduction Tmentioning
confidence: 99%
“…The fruit has traditionally been used in Korean folk medicine for the treatment of inflammatory disorders and cancer. The intense dark red hue reflects an abundance of anthocyanin pigments the anti-cancer activities of which have been reported in vitro and in vivo (4)(5)(6). Therefore, we postulated that the anthocyanins are major components for the anti-cancer activities of the Meoru.…”
Section: Introductionmentioning
confidence: 78%
“…The phosphorylation levels of these two sites are dramatically increased upon stimulation of NF-kB activity. 29,30 Moreover, studies show that tumor cell apoptosis induced by anticancer reagents is associated with decreased p65 phosphorylation at Ser536 residue, [31][32][33] suggesting that p65 Ser536 phosphorylation is important for maintaining cancer cell survival and can be inhibited by anticancer reagents. In this study we showed that not only phosphorylation of Ser536 but also phosphorylation of Ser468 is downregulated during HDAC inhibitor-induced apoptosis of EC cells.…”
Section: Discussionmentioning
confidence: 99%